Level of public knowledge on the principle of DAGUSIBU in antacid drugs at thalhah pharmacy - Herman, Herman; Lau, Sulfiyana H Ambo (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2025)
Introduction: Antacids are commonly used over-the-counter medications for treating gastritis, yet public knowledge regarding their proper use remains limited. The DAGUSIBU (Obtain, Use, Store, Dispose) campaign by the Indonesian Pharmacists Association aims to improve rational drug use among the community. However, initial observation at Thalhah Pharmacy in Makassar revealed a lack of counseling related to DAGUSIBU principles. This study aims to assess the level of public knowledge regarding the DAGUSIBU principles related to antacid use at Thalhah Pharmacy. Method: This was a descriptive study using a survey method. A total of 48 respondents were selected from 90 pharmacy visitors through accidental sampling using the Slovin formula. Data were collected using a Likert-scale questionnaire and analyzed using Microsoft Excel, with results presented in percentage tables and categorized into three levels: good, fair, and poor. Results: Findings show that 73.25% of respondents had good knowledge, 20.82% had fair knowledge, and 5.91% had poor knowledge of DAGUSIBU principles. Knowledge of obtaining antacids was good (77.8%), while use (59%), storage (58%), and disposal (43.7%) scored moderately. Conclusion: The public demonstrates adequate knowledge in obtaining antacids, but further education is needed in the areas of usage, storage, and disposal to support safe and responsible self-medication practices